Evaluation of Palm Kernel Cake Fermented by Aspergillus niger as Substitute for Soybean Meal Protein in the Diet of Broiler - Mirnawati; Rizal, Yose; Marlida, Yetti; Kompiang, I. Putu (International Journal of Poultry Science, 2011)
An experiment was conducted for the evaluation of Palm Kernel Cake Fermented (PKCF) by Aspergillus niger as a substitute for soybean meal protein in the diet of broiler. The experiment used a Complete Randomize Design (CRD) with 6 treatments and 4 replications. The treatments were arranged as follows: 1) 0% basic ration (0% PKCF), 2) 20% substitution of soybean meal protein with PKCF, 3) 40% substitution of soybean meal protein with PKCF, 4) 60% substitution of soybean meal protein with PKCF, 5) 80% substitution of soybean meal with PKCF, 6) 100% substitution of soybean meal with PKCF. The ration were formulated in iso protein 22% and iso caloric 3000 k cal/kg ration. This study used a completely randomized design with six treatments and four replications. The parameters of this study were feed consumption, body weight gained, feed conversion and percentage of carcass. The result of this study showed that feed consumption, body weight gained, feed conversion and percentage of carcase were not significantly affected (p>0.05) by any treatment. In conclusion the Palm Kernel Cake Fermented (PKCF) by Aspergillus niger can be 100% a substitute of soybean meal protein or 17% in broiler ration.